The use of the Dobeshi wavelet w APPLICATION OF THE DOBESHI WAVELET METHOD IN DIGITAL PROCESSING OF SIGNALS: APPLICATION OF THE DOBESHI WAVELET METHOD IN DIGITAL PROCESSING OF SIGNALS - Mullajonova, Fotima; Mullajonova, Fotima (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article is devoted to the construction of Weivlet models, which are considered important in digital processing of Biomedicine signals. These models were built using Dobeshi veyvlets. Dobeshi Weyvlet models have high accuracy in digital performance of Biomedicine signals, this makes a significant contribution to the patient's disease response to provide useful information on how physicians make decisions. As an example, the initial experimental data of its signal from human body sensors were obtained, and on the basis of these data, Dobeshi Weyvlet models were built and their errors were assessed. It is known that Dobeshi wavelets were used in order to reduce signals error, and as a result, error reduction was achieved.